TENSES IN ENGLISH: A COMPREHENSIVE ANALYSIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper provides an in-depth examination of tenses in the English language, exploring their forms, functions, and usage. It delves into the complexities of simple, continuous, perfect, and perfect continuous tenses, highlighting their role in conveying time, aspect, and mood. The paper further analyzes the interaction of tenses with adverbs of time and explores common errors made by English language learners. Finally, it discusses the evolving nature of tenses in contemporary English and implications for language teaching.